Natural convection effects on heat and mass transfer in a curvilinear triangular cavity - Rahman, M. M.; Öztop, Hakan Fehmi; Ahsan, A.; Orfi, J. (Pergamon-Elsevier Science Ltd, 2012)
Finite element method is used in this study to analyze the effects of buoyancy ratio and Lewis number on heat and mass transfer in a triangular cavity with zig-zag shaped bottom wall. Buoyancy ratio is defined as the ratio of Grashof number of solutal and thermal. Inclined walls of the cavity have lower temperature and concentration according to zig-zag shaped bottom wall. Enclosed space consists mostly of an absorber plate and two inclined glass covers that form a cavity. Both high temperature and high concentrations are applied to bottom corrugated wall. Computations were done for different values of buoyancy ratio (-10 <= Br <= 10), Lewis number (0.1 <= Le <= 20) and thermal Rayleigh number (10(4) <= Ra-T <= 10(6)). Streamlines, isotherms, iso-concentration, average Nusselt and Sherwood numbers are obtained. It is found that average Nusselt and Sherwood numbers increase by 89.18% and 101.91% respectively as Br increases from -10 to 20 at Ra-T = 10(6). Also, average Nusselt decreases by 16.22% and Sherwood numbers increases by 144.84% as Le increases from 0.1 to 20 at this Rayleigh number. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Double-diffusive; Natural convection; Finite element method; Triangular cavity; Absorber plate; Inclined glass covers